2015
DOI: 10.1093/ijnp/pyu102
|View full text |Cite
|
Sign up to set email alerts
|

The Mood Stabilizer Lithium Potentiates the Antidepressant-Like Effects and Ameliorates Oxidative Stress Induced by Acute Ketamine in a Mouse Model of Stress

Abstract: Background:Evidence suggests that mammalian target of rapamycin activation mediates ketamine’s rapid but transient antidepressant effects and that glycogen synthase kinase-3β inhibits this pathway. However, ketamine has associated psychotomimetic effects and a high risk of abuse. The mood stabilizer lithium is a glycogen synthase kinase-3 inhibitor with strong antisuicidal properties. Here, we used a mouse stress model to investigate whether adjunct lithium treatment would potentiate ketamine’s antidepressant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 54 publications
(75 reference statements)
3
44
0
1
Order By: Relevance
“…Compatibly, Petit-Paitel et al have depicted that either pharmacological or genetically inhibition of GSK-3␤ (LiCl and kenpaullone, and RNA interference) could abrogate MPP+ mediated mitochondrial membrane potential changes and subsequent caspase-9 and -3 activations [101]. As mentioned, GSK-3␤ is involved in oxidative damages seen in PD, therefore fighting against oxidative stress by GSK-3␤ inhibitors is another potential treatment choice for PD, in accordance to this theory evidences are available showing that different GSK-3␤ inhibitors such as lithium and BIP-135 could abrogate oxidative damages in neuronal models of oxidative stress [160,161]. Preventing ER stress induction is another possible way that might contribute to the efficiency of GSK-3 inhibitors against PD; persistently it has been shown that pretreatment with GSK-3 inhibitors such as lithium significantly reduces CHOP expression [162].…”
Section: Gsk-3␤ Inhibition As a Therapeutic Potential For Pdmentioning
confidence: 71%
“…Compatibly, Petit-Paitel et al have depicted that either pharmacological or genetically inhibition of GSK-3␤ (LiCl and kenpaullone, and RNA interference) could abrogate MPP+ mediated mitochondrial membrane potential changes and subsequent caspase-9 and -3 activations [101]. As mentioned, GSK-3␤ is involved in oxidative damages seen in PD, therefore fighting against oxidative stress by GSK-3␤ inhibitors is another potential treatment choice for PD, in accordance to this theory evidences are available showing that different GSK-3␤ inhibitors such as lithium and BIP-135 could abrogate oxidative damages in neuronal models of oxidative stress [160,161]. Preventing ER stress induction is another possible way that might contribute to the efficiency of GSK-3 inhibitors against PD; persistently it has been shown that pretreatment with GSK-3 inhibitors such as lithium significantly reduces CHOP expression [162].…”
Section: Gsk-3␤ Inhibition As a Therapeutic Potential For Pdmentioning
confidence: 71%
“…Ketamine can induce rapid antidepressant effects in depressed patients with mood disorders (Newport et al, 2015; Niciu et al, 2014; Scheuing et al, 2015) and the antidepressant mechanism of action of ketamine is linked to GSK3 inhibition (Beurel et al, 2011; Chiu et al, 2014; Ghasemi et al, 2010; Liu et al, 2013; Yang et al, 2013; Zhou et al, 2014). Here we found that up-regulation of IGF2 expression in mouse hippocampus appears to contribute to the GSK3 inhibition-dependent antidepressant effect of ketamine in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine treatment fails to induce an antidepressant effect in GSK3 knockin mice, demonstrating the necessity for ketamine-induced inhibitory serine-phosphorylation of GSK3 for this effect (Beurel et al, 2011). Further studies showed that administration of GSK3 inhibitors enhanced the antidepressant effects of ketamine (Chiu et al, 2014; Ghasemi et al, 2010; Liu et al, 2013). Thus, ketamine-induced inhibition of GSK3 is linked to its antidepressant action, but it remains unknown how this contributes to the antidepressant effects of ketamine (Zunszain et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of flupirtine (a centrally acting, non-opioid analgesic) attenuates the stress-induced deleterious effects by decreasing GSK-3β activity, suggesting the role of activation of GSK-3β signaling pathways during stress induction [14]. The administration of lithium, a GSK-3β inhibitor, potentiates the antidepressant-like effects of ketamine in a mouse model of stress [15]. However, there has also been a study showing that the administration of a GSK-3β inhibitor does not affect the immobility time in chronic unpredictable stress-subjected animals [16].…”
Section: Introductionmentioning
confidence: 99%